Implementation Of User Experience Questionnaire (UEQ) To Evaluate User Experience Of Edlink Application - Eka Wijaya Paula; Aulyah Zakilah Ifani; Agunawan (Program Studi Teknik Komputer, 2024)
The Nobel Institute of Technology and Business Indonesia uses EdLink in learning management, but the system has not been validated through user experience, so it is not known to what extent student satisfaction is in using it. This study was made to test student satisfaction in using the information system. Through the User Experience Quissionare (UEQ) method to 100 students as respondents. The UEQ assessment goes through 6 aspects, including efficiency, attractiveness, accuracy, clarity, stimulation, and novelty. The results obtained from the aspect of the accident received the lowest score among other aspects. While the highest aspect is the efficiency aspect.